STUDYING RENOVATION METHODS OF WORN DETAILS OF AGRICULTURAL MACHINERY - Ivankova, O. V.; Garashchuk, O. V.; Kutsenko, V. I.; Shcherbyna, V. V.; Chyzhevsʹkyy, D. V.; Babych, Ya. V.; Tykhonov, M. O. (Scientific Progress & Innovations, 2020)
An important direction of technical service industry is the development of rational technologies for the restoration of worn parts of agricultural machinery. The modern branch of technical service requires the development of new technologies for strengthening the surfaces of machine parts to improve their perfor-mance. The purpose of the work is to identify the optimal method for renovating worn parts of agricultural machinery, forming a wear-resistant surface structure, having a low process temperature and practically eliminating the formation of thermal impact zone. It must have high economic and environmental parameters of the technological process. During the research we analyzed data from literature sources, the experience of leading technical service enterprises, described and compared the characteristics of technological processes of details’ renovation; generalized the results of analysis and comparison of characteristics and developed conclusions as to the optimal method of restoration of machine worn parts. Based on the results of analyzing literature sources and the experience of advanced technical service enterprises, the advantages and disadvantages of the method of electric spark alloy were revealed. The possibilities of using it to restore worn surfaces of agricultural machinery parts have been clarified. It has been found that the method of electrical spark alloying is optimal for the repair of details. It provides high strength of adhesion of the applied layer; does not have a thermal effect on the detail; provides an opportunity of applying local strengthening of separate detail parts without dismantling the machine unit. Electrical spark alloying is characterized by: low energy consumption, small and mobile technological equipment, the process is environmentally friendly. It outperforms most traditional methods of restoring parts. The trends in the development of electric spark alloying technologies involve the replacement of expensive refractory components of electrode materials with new, cheaper, but effective. This makes it promising and quite attractive for research and application in production to strengthen and restore worn machine parts. Taking into account the simplicity of the equipment used for electric spark finishing, this method of renovation can be recommended for use in technical service workshops.